A revision of the genus Trithrinax (Cryosophileae, Coryphoideae, Arecaceae) - Cano, Ángela; Perret, Mathieu; Stauffer, Fred W. (Phytotaxa, 2013)
The palm genus Trithrinax is revised and three species and four varieties are accepted (T. brasiliensis var. brasiliensis, T. brasiliensis var. acanthocoma, T. campestris, T. schizophylla var. schizophylla and T. schizophylla var. biflabellata comb. nov.). This taxonomic treatment presents detailed and complete description of all taxa, based on the studies of natural populations in Argentina, Brazil and Paraguay, the morphological analysis of herbarium specimens (including all available types) and an exhaustive literature research. Illustrations are presented for all taxa and identification keys to the species and varieties are proposed. Species descriptions include updated distribution maps, information about their ecology, taxonomic notes and a compilation of common names and uses. The conservation status assessment reveals an important level of threatening for all taxa, ranging from vulnerable (VU) to endangered (EN), mainly due to the decline of the area of occupancy and the quality of habitat.